Translatorska recepcja powieści Pawła Sanajewa Pochowajcie mnie pod podłogą - Jermaszowa, Irina (Przegląd Rusycystyczny, 2012)
Irina Jermaszowa Uniwersytet Adama Mickiewicza, Poznań, Poland erm-irka@yandex.ru ПЕРЕВОДЧЕСКАЯ РЕЦЕПЦИЯ ПОВЕСТИ ПАВЛА САНАЕВА ПОХОРОНИТЕ МЕНЯ ПОД ПЛИНТУСОМ Резюме Предметом моих исследований стал польский перевод известной в России книги Павла Санаева Похороните меня за плинтусом. Название польской версии — Pochowajcie mnie pod podłogą. Феномен популярности произведения и ее автора объясняется не только художественной стороной, но скандальной. Сюжет частично построен на автобиографии писателя, который родом из известной актерской семьи. Описанная история удостоилась экранизации и нескольких театральных постановок, а также перевода на иностранные языки, в том числе — польский. В статье представляю результаты сравнительного анализа (оригинала и перевода) и рецепцию произведения в Польше. THE TRANSLATION RECEPTION OF PAVEL SANAEV’S BURy ME BEHIND THE BASEBOARD Summary The Polish translation of a popular in Russia book Bury me under a Plinth (in Polish ver-sion: Pochowajcie mnie pod podłogą) by Pavel Sanajev was the main area of my research. The phenomenon of the popularity of this work and its author results not only from the artistic but also scandalous side of the book. The plot is partially based on the autobiogra-phy of the writer who grew up in the well known family of actors. The story described in the book has been successfully adapted by numerous film and theatre directors. Besides, it has been translated into many languages, including Polish. The article presents the results of a comparative anaysis (Russian version vs Polish translation) and the reception of the work in Poland